On the Frontline: Exploring the Perceptions of Lahore's Innercity School Teachers Regarding Children Problems - Nazish IMRAN; Atif RAHMAN; Nakhshab CHAUDHRY; Aftab ASIF (Tehran University of Medical Sciences, 2018)
Background: We aimed to explore inner city school teachers' perceptions of problems faced in schools, it causes and role of schools and teachers in promoting child social and emotional well-being, using qualitative approach. Methods: Following ethical approval and informed consent, In-depth interviews were conducted in 2017 with twenty teachers belonging to four private schools in inner city area of Provincial capital, Lahore, Pakistan. Inclusion criteria were at least 12 years of formal education and minimum of 5 years' experience in teaching profession. Framework Analysis was used to analyze data. Results: Teachers identified learning problems, inattention, disobedience, aggression, lying & disrespect as the most commonly encountered problems of children, with very few teachers mentioning emotional difficulties. Teachers view the family, parenting practices and home environment alongside media (in particular social media) as being the main causes of child behavioral problems. With prompts, however, they did identify various school and teacher-related factors having negative impact on children. Fair conceptualization of good school and good teacher was observed. Need for teacher awareness and training for strategies promoting child emotional and social wellbeing was highlighted. Conclusion: As perceived by teachers, children studying in inner city schools have several behaviour problems. Study results and the gaps identified will help in ensuring that teachers receive training targeted towards their needs. Findings of the study also substantiate the need for targeting whole school-wide preventive approach as efforts begin to implement school mental health initiative in Pakistan.